2008
DOI: 10.1590/s0102-09352008000200013
|View full text |Cite
|
Sign up to set email alerts
|

Espessura corneana mensurada pelo paquímetro ultra-sônico e pelo microscópio especular Topcon SP-2000P em gatos

Abstract: The central corneal thickness of 13 normal cats was evaluated by a Topcon SP-2000P noncontact specular microscope and by an ultrasonic pachymetry was evaluated. An increase on the corneal thickness measured by ultrasonic pachymetry as compared to the specular microscope was observed. Keywords: cat, corneal thickness, pachymetry, specular INTRODUÇÃOA fisiologia das células endoteliais da córnea dos felinos tem características similares às dos humanos, sendo usada comumente como um modelo para estudos endoteliai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…In the present study, the mean CCT value was thicker than what has been reported in the literature using the ultrasonic pachymetry: 569 ± 36 μm, 25 578 ± 64 μm, 26 546 ± 48 μm 27 and 606 ± 77 μm, 28 right eye 515 ± 73 μm, and left eye 523 ± 68 μm 29 . This difference was also observed by Park et al 30 comparing the CCT offered by the Galilei and ultrasonic pachymetry in humans.…”
Section: Discussionsupporting
confidence: 71%
“…In the present study, the mean CCT value was thicker than what has been reported in the literature using the ultrasonic pachymetry: 569 ± 36 μm, 25 578 ± 64 μm, 26 546 ± 48 μm 27 and 606 ± 77 μm, 28 right eye 515 ± 73 μm, and left eye 523 ± 68 μm 29 . This difference was also observed by Park et al 30 comparing the CCT offered by the Galilei and ultrasonic pachymetry in humans.…”
Section: Discussionsupporting
confidence: 71%
“…There are many devices available in clinical practice for measuring corneal pachymetry and keratometry. [8][9][10][11] In cats, corneal thickness has been measured using optical pachymetry, 12 ultrasonic pachymetry, [13][14][15][16][17] ultrasonic biomicroscopy, 18,19 specular microscopy, 17 optical coherence tomography, 20,21 single Scheimpflug device (Pentacam-HR), 20 and dual Scheimpflug device (Galilei). 22 Keratometry has been described in cats using a keratometer 18,23,24 and Galilei.…”
Section: Introductionmentioning
confidence: 99%